An Analysis of the Citation Practices of Undergraduate Spanish Students - Luzón, María José (Journal of Academic Writing, 2015)
One basic skill of academic writers is to be able to locate their claims within a disciplinary framework. However, undergraduate students find it difficult to integrate sources into their own writing successfully, which often results in inappropriate textual borrowing and poor referencing. The aim of the research reported here was to identify problematic or inappropriate use of sources in texts produced by undergraduate Spanish students and examine the reasons for these unacceptable citation practices. For this purpose, I analyzed a learner corpus consisting of 35 literature reviews written by students of an EAP subject in the third year of a Bachelor’s Degree in English Studies. The results suggest that their inappropriate use of sources arises mainly from three factors: (i) an unawareness of the dialogic nature of academic texts and of the functions of citation in these texts; (ii) low linguistic level and low level of academic literacy regarding the procedures involved in paraphrasing and synthesizing; (iii) lack of familiarity with the language of citations.